Evaluasi Program Pelatihan Permaculture Design Course di Kebun Hanif - Hartono, Choirussahla Aqiilah; Renaldi, Eddy (Universitas Galuh, 2025)
Permaculture is an agricultural design approach that integrates social, economic, and environmental considerations. To develop sustainable agricultural practices like permaculture, specialized training is necessary due to its distinct differences from conventional farming methods. Kebun Hanif is one of the locations that applies permaculture design concepts and conducts related training programs. This study aims to evaluate the implementation of the Permaculture Design Course (PDC) at Kebun Hanif and assess the program’s overall effectiveness. The research employs both qualitative and quantitative approaches, using the Context, Input, Process, and Product (CIPP) evaluation model. Data collection methods include distributing questionnaires, conducting in-depth interviews, and reviewing documents. The results indicate that the PDC at Kebun Hanif, an intensive program that began in early 2022, teaches permaculture principles through an approach based on Islamic values. The evaluation, using the CIPP model, yielded positive outcomes across all aspects: context, input, process, and product. The context evaluation showed an 83% satisfaction rate, demonstrating the program's relevance to local needs. The input evaluation scored 84%, highlighting sufficient resource allocation and planning. The process evaluation scored 80%, indicating that the program was implemented as planned, though there is room for improvement. The product evaluation revealed an 80% success rate, reflecting the program’s effectiveness in achieving its goals and in the application of permaculture concepts by participants.